(untitled) (Asian Journal of Medical and Biological Research, 2022)
The severity of Coronavirus disease-2019 (COVID-19) varies among individuals and some influential factors leads to critical infections and death. This study aimed to assess various clinical data of hospitalized patients and identify the determinants of critical COVID-19 infection. This was a cross-sectional study among hospitalized COVID-19 patients confirmed by reverse transcription polymerase chain reaction (RT-PCR). Data was collected from a single Centre between January to April 2021 by experienced physicians of Ad-din Medical College Hospital. All of the laboratory tests were performed by technical experts and the data was analyzed by Statistical package for the social sciences software. Among the study participants 25% were Intensive care unit (ICU) patients and the mean age of them were higher (59 years) than non-ICU (55 years) patients. Our analysis has identified diabetes mellitus (AOR=2.5, 95%CI: 1.1-5.4) and ischemic heart disease (AOR=3.1, 95%CI: 1.1-8.9) as significant predictor of critical outcome (ICU admission). Anemia (AOR=3.3, 95%CI: 1.5-7.4), lymphopenia (AOR=2.9, 95%CI: 1.2-7.1), and thrombocytopenia (AOR=4.2, 95%CI: 2.7-12.9) was also associated critical outcome. Biomarkers of kidney injury (creatinine, blood urea nitrogen), liver damage (alanine transaminase, aspartate aminotransferase, fibrinogen) and electrolyte imbalance (sodium and potassium level) were also significantly associated with critical infection. A higher d-dimer level (≥2.5) was the most important predictor (AOR=11.5, 95%CI: 5.4-24.6) of critical COVID 19 infections. The study has revealed socio-demographic, comorbidity, and radiological risk factors of critical COVID-19 infections. The identified risk factors would be considered for decision making during the treatment process. Asian J. Med. Biol. Res. 2022, 8 (1), 16-23